The Continuity Of Shinto Theatrical Dance in Aging Society Era: Case Study Of Kagura Dance Revitalization in Matsumae City Hokkaido - Serang, Manuela Bernarda; Srimulyani, Nunuk Endah (KIRYOKU, 2024)
The Kagura dance is a sacred, theatrical dance to entertain the Shinto gods. In several areas, including the city of Matsumae, Hokkaido island, this dance is threatened with extinction due to a lack of the next generation. Using an ethnographic approach, this research aims to describe the development of the Kagura dance and efforts to revitalize the dance amidst the aging society phenomenon that has hit Japan. The data collection techniques used were observation and in-depth interviews. Researchers observed the preparation process for the dance festival for six months and conducted interviews with Shinto priests, local Education and Culture Service employees, and hotel employees to gather data. The research results show that the potential extinction of the Kagura dance is mainly caused by the reduction in the young population because most of the population urbanizes to study and work in big cities. The revitalization strategy that has been carried out is  establishing  the  Kagura  Matsumae  preservation body which oversees the Matsumae shrine, the Kagura Kiyobe Preservation Society, the Haraguchi Preservation Society, and teaching the locality of Matsumae City from elementary to middle school students. The effort has a positive impact on student's awareness of preserving Kagura dance. Some students have joined and become the main members of the Kagura Preservation Body. Since the majority of people moved to the urban areas, the revitalization effort has not been completely successful. However, it can be seen that the city government's awareness and efforts are very high to maintain traditional culture.